Maturity status in male child and adolescent athletes - Moore, S. A.; Moore, M.; Klentrou, P.; Sullivan, P.; Falk, B. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: Early-maturing individuals may be at an advantage in some sports. The purpose of this study was to compare maturity status between competitive male child (10-12 years old) and adolescent (14-16 years old) athletes and minimally-active, age-matched controls. METHODS: In total, 224 males were included in the study. Children (n=115) included minimally-active boys (n=34), soccer players (n=26), gymnasts (n=25) and hockey players (n=30). Adolescents (n=109) included minimally-active adolescents (n=31), soccer players (n=30), gymnasts (n=17) and hockey players (n=31). Sexual maturity was assessed using secondary sex characteristics and salivary testosterone concentration (sT). Skeletal age was also assessed, using quantitative ultrasound (Sunlight BonAgeTM). RESULTS: Within each age group, no differences were observed between sport groups in chronological age, sT or pubertal age. In children, hockey players were more skeletally mature (12.43±1.36 years) than all other groups (11.0±1.0; 11.6±1.4 and 11.7±1.4 years for soccer, gymnasts and controls, respectively). In adolescents, hockey players and gymnasts had higher skeletal maturity (16.8±1.5 and 16.9±1.6 years, respectively; P<0.05) than controls (15.99±1.13 years). CONCLUSION: While sexual and hormonal maturity does not appear to differ between similar-aged athletes of different sports, the results suggest greater skeletal maturity in hockey players, even before puberty.